The impact of computerisation on clerical work in the finance sector : case studies of two large life assurance companies in the Western Cape, 1955-1985 - Hartman, Nadia (Department of Sociology, 2015)
The association of microelectronics and the office and its consequences specifically for life assurance companies is the central focus of this thesis. The original intention was to survey the impact of computerisation on clerical work in the Finance Sector, focusing specifically on banks, building societies and life assurance companies. The Finance Sector was chosen because it is the largest employer of clerical workers after the civil service and was also the most advanced user of computers in commerce. A survey of the literature on computerisation and clerical work revealed that a comparison of job categories prior to and following computerisation was necessary if the full impact of the technology was to be assessed. However, after several months of research it became evident that a comparison of job categories in the pre- and post-computer eras in all parts of the Finance Sector - banks, building societies and assurance companies - would make for an impossibly long exercise in the thesis if all were researched comparably. It was decided to concentrate on two very large life assurance companies in South Africa who were among the first to computerise in the country. Comparability was enhanced by the fact that both company headquarters were in Cape Town and therefore accessible for in-depth and repeated interviewing. This together with the fact that the companies were among the largest employers of clerical labour in the Western Cape made the choice natural and inevitable.